Peran Lagu Islami pada Perkembangan Spritual Anak Usia Dini di RA Arafah Sipolu-Polu Kecamatan Panyabungan Kabupaten Mandailing Natal - NST, Silva Hidayah; Nur, Kholidah; Harahap, Sartika Dewi (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the role of Islamic songs in the spiritual development of early childhood in RA Arafah Sipolu-polu, Panyabungan District, Mandailing Natal Regency. This study uses a qualitative descriptive method. The data used in this study include observations, interviews and documentation. The data analysis techniques used are data reduction, data presentation, and data verification. The results of the data analysis show that Islamic songs have a role in helping early childhood in introducing the concept of divinity and religion, understanding and values of Islam, increasing love for Allah and the Messenger, getting used to worship from an early age, providing peace of mind to those who listen to it, and helping in the formation of character and morals in early childhood. Supporting factors include the active involvement of teachers and parents, the use of appropriate media, and a supportive learning environment. Conversely, inhibiting factors include a lack of support from parents, limited access to appropriate songs, and a lack of understanding of the importance of songs in early childhood learning. Islamic songs contain various spiritual values that help children understand and practice religious teachings. Some of the spiritual values contained in Islamic songs include: Faith Education, Worship Education and Moral Education